2021
DOI: 10.1016/s2666-5247(20)30221-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of human coronaviruses in Belgian primary care and hospitals, 2015–20: a surveillance study

Abstract: Background Seasonal human coronaviruses (hCoVs) broadly circulate in humans. Their epidemiology and effect on the spread of emerging coronaviruses has been neglected thus far. We aimed to elucidate the epidemiology and burden of disease of seasonal hCoVs OC43, NL63, and 229E in patients in primary care and hospitals in Belgium between 2015 and 2020. Methods We retrospectively analysed data from the national influenza surveillance networks in Belgium during the winter se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 27 publications
4
37
2
Order By: Relevance
“…Numerous studies have looked at the age pattern of HCoV patients presenting to hospital and healthcare settings, and predominantly found that the burden of disease is higher in younger children and the elderly [43][44][45] . However, it is likely that these age groups may have more severe symptoms and are therefore more likely to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have looked at the age pattern of HCoV patients presenting to hospital and healthcare settings, and predominantly found that the burden of disease is higher in younger children and the elderly [43][44][45] . However, it is likely that these age groups may have more severe symptoms and are therefore more likely to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as we gained more valuable data from population-based studies that utilized molecular methods, there was still not much attention paid to these viruses and their possible role in various clinical presentations, possible because very little was known regarding their exact role in respiratory illnesses ( 15 , 18 , 19 ). And while recent studies on hospitalized patients have confirmed the important role of sCoVs and their global circulation ( 20 ), we still lack pertinent data on the frequency and seasonality in the broader community context ( 21 ).…”
Section: An Overview and Global Trendsmentioning
confidence: 99%
“…In any case, serological surveys on the population level will be indispensable for establishing true sCoV infection burden and the respective age distribution, as well as appraising the prospect of coveted cross-protective immunity. Findings from a recent study by Fischer et al endorse the use of national influenza surveillance systems for sCoV early detection and monitoring, which will enable a an enhanced estimation of the burden of disease, and also aid in tracking emerging coronaviruses such as SARS-CoV-2 ( 20 ).…”
Section: An Overview and Global Trendsmentioning
confidence: 99%
“…HCoV-OC43 is the most prevalent eHCoV and accounts, together with HCoV-229E, for about 30% of all common colds. This explains the high seroprevalence for these two viruses in the adult population ( 3 , 4 , 9 12 ).…”
Section: Introductionmentioning
confidence: 98%